2011
DOI: 10.1016/j.jtbi.2010.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal modelling of the Hes1 and p53-Mdm2 intracellular signalling pathways

Abstract: The correct localisation of transcription factors is vitally important for the proper functioning of many intracellular signalling pathways. Experimental data has shown that many pathways exhibit oscillations in concentrations of the substances involved, both temporally and spatially. Negative feedback loops are important components of these oscillations, providing fine regulation for the factors involved. In this paper we consider mathematical models of two such pathways -Hes1 and p53-Mdm2.Building on previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 42 publications
2
86
1
Order By: Relevance
“…The effect of low molecule numbers in Monk's DDE model of the Hes1 GRN was explored in Barrio et al (2006). A spatio-temporal model of the Hes1 GRN, using a partial differential equation (PDE) approach, was presented in Sturrock et al (2011) and extensions of this model were considered in Sturrock et al (2012). A spatial stochastic model of the Hes1 GRN in embryonic stem cells was studied in Sturrock et al (2013) -this model was derived using mass action kinetics and its mean behaviour was studied in Sturrock et al (2014b).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of low molecule numbers in Monk's DDE model of the Hes1 GRN was explored in Barrio et al (2006). A spatio-temporal model of the Hes1 GRN, using a partial differential equation (PDE) approach, was presented in Sturrock et al (2011) and extensions of this model were considered in Sturrock et al (2012). A spatial stochastic model of the Hes1 GRN in embryonic stem cells was studied in Sturrock et al (2013) -this model was derived using mass action kinetics and its mean behaviour was studied in Sturrock et al (2014b).…”
Section: Introductionmentioning
confidence: 99%
“…In (see [28,13]) models without spatial localization of reactions were considered. Spatial dependence of intracellular transport was introduced in [20,19,26,29,11,10,31,32,8]. Recent developments have been obtained by Cangiani et al [3] and Dimitrio et al [9].…”
Section: Need Of Numerical Modelsmentioning
confidence: 99%
“…Experimental data have shown that many regulatory networks exhibit temporal oscillations of concentrations of the substances involved [70,83]. Intracellular negative feedback loops are important components of these oscillations, providing fine regulation of the factors involved.…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular negative feedback loops are important components of these oscillations, providing fine regulation of the factors involved. Two examples of such pathways, Hes1 and p53, which involve oscillations, are particularly studied in the literature [70,83]. These proteins act by binding to specific DNA sequences in the nucleus, either promoting or inhibiting the binding of RNA polymerase to DNA and are of fundamental importance for cellular normal homeostasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation